Potential of Sodium-Glucose Cotransporter Inhibitors as Agents for Prevention of Ischemic and Reperfusion Kidney Injury: Life Sciences-Health - Yu. Poltev, Vladimir; V. Pokrovskii, Mikhail; B. Kovalenko, Igor; A. Kostina, Darya (International Journal of Life Science and Pharma Research, 2022)
Sodium-glucose cotransporter 2 inhibitors are a relatively new class of glucose-lowering agents with significant advantages over other groups due to their good safety profile and protective effects on the cardiovascular system and kidneys. Today, the question of their ability to prevent and reduce the severity of acute kidney injury remains relevant. The primary objective of the study is to investigate the Potential of Sodium-Glucose Cotransporter Inhibitors as Agents for the Prevention of Ischemic and Reperfusion Kidney Injury. To gratify that objective, the experiment was performed on 80 Wistar line male rats. Acute kidney injury was simulated by reproducing a bilateral 40-minute renal ischemia-reperfusion. sodium-glucose cotransporter inhibitors were administered before surgery: dapagliflozin at doses of 0.5 mg/kg and 1 mg/kg, canagliflozin - 8.6 mg/kg and 25.7 mg/kg, empagliflozin - 1 mg/kg and 2 mg/kg. The renoprotective effects were evaluated after 72 hours based on the following parameters: serum creatinine and urea concentrations, glomerular filtration rate and fractional sodium excretion, as well as the level of renal microcirculation. Based on the results acquired, Preliminary administration of dapagliflozin, canagliflozin and empagliflozin led to a statistically significant decrease in the level of serum creatinine concentration and fractional sodium excretion, as well as an increase in the glomerular filtration rate, compared with the control group. The results demonstrated their dosedependent effect and ability to improve the parameters of renal microcirculation. Plus, the results of the study demonstrate a high dose-dependent renoprotective potential of sodium-glucose cotransporter 2 inhibitors (dapagliflozin, canagliflozin and empagliflozin) on a model of bilateral renal ischemia-reperfusion. The results of this study can greatly contribute to the respective field.